ON THE CRITIAL VELOCITY OF A VEHICLE MOVING ON THE BRIDGE - Khang, Nguyễn Văn; Vân Hương, Nguyễn Thị; Phong, Nguyễn Đức (Vietnam Journal of Science and Technology, 2016)
Vibration model of a vehicle on the bridge is modeled by a mass - spring - damper system moving on an elastic beam. This paper presents the results of a new study on determining the critical velocity of a vehicle moving on the beam bridge. The critical velocity of the vehicle calculated according to the new model is much smaller than that calculated according to the old formula.